Pancreatic cancer in chronic pancreatitis; aetiology, incidence, and early detection - Raimondi, Sara; Lowenfels, Albert B.; Morselli-Labate, Antonio M.; Maisonneuve, Patrick; Pezzilli, Raffaele (Baillière's best practice & research. Clinical gastroenterology, 2010)
Acute pancreatitis, chronic pancreatitis and pancreatic cancer are responsible for most of the burden of exocrine pancreatic disease. Glandular damage from recurrent bouts of acute pancreatitis can lead to irreversible changes characteristic of chronic pancreatitis. In recent decades accumulating evidence has defined longstanding pre-existing chronic pancreatitis as a strong risk factor for pancreatic cancer. The lag period between diagnosis of chronic pancreatitis and pancreatic cancer is usually one or two decades: pancreatitis appearing a year or two before the diagnosis of pancreatic cancer is often the result of tumour-related ductal obstruction. The risk of developing pancreatic cancer appears to be highest in rare types of pancreatitis with an early onset, such as hereditary pancreatitis and tropical pancreatitis. Even though there is a strong link between chronic pancreatitis and pancreatic cancer, over a 20 year period only around five percent of patients with chronic pancreatitis will develop pancreatic cancer. Until the development of more sophisticated screening procedures, screening is not recommended for patients with chronic pancreatitis.